Pengaruh Kualitas Makanan, Harga, dan Menu terhadap Pembelian Ulang di Tjokro Restoran - Tri Amboro, Fajar (Multmedia Nusantara Politeknik, 2025)
The decline in guest visits to Tjokro Restaurant, Grand Tjokro Hotel Yogyakarta, has become a critical concernamid the competitive hospitality industry. This study aims to analyze the influence of food quality, pricing, and menu variety on guests’ repeat purchase decisions, with satisfaction as a mediating variable. The researchemployed a quantitative approach, using ques tionnaires distributed to restaurant guests. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between variables. The findings reveal that food quality, price, and menu variety significantly affect guest satisfaction. Furthermore, guest satisfaction plays a key mediating role in enhancing repeat purchase intention. These results indicate that improving food quality, applying appropriate pricing strategies, and innovating menu variations can directly and indirectly increase customer loyalty. The practical implication of this study is to encourage restaurant management to prioritize these elements in order to promote sustainable guest satisfaction and loyalty. This research also highlights that negative customer reviews can be transformed into strategic opportunities for improving servicequality.